Self-Advocacy and Conflict Resolution Training Among College Students with Learning Disabilities and/or Attention Deficit Hyperactivity Disorder - Chambers, Alex W.; Holzberg, Debra G. (International Journal of Rehabilitation and Special Education (IJRSE), 2025)
For students with learning disabilities (LD), and /or attention deficit hyperactivity disorder (ADHD) the transition from secondary to postsecondary education presents additional challenges, particularly in acquiring and utilizing academic accommodations. Self-advocacy skills are essential for successfully navigating these educational environments. This study investigated the impact of Self-Advocacy and Conflict Resolution (SACR) instruction, taught in a small group setting, on the ability of three college students with LD and/or ADHD to request and negotiate academic accommodations. Using a single-subject, multiple probe, ABC design, findings indicated an increase in level and trend between SACR instruction and students’ improved accommodation requests during role-play and generalization conditions. Social validity survey data indicated participants found the intervention helped them explain their needs and better understand their disabilities. Limitations, implications for practice, and suggestions for future research are discussed.
Keywords: self-advocacy; post-secondary education; learning disabilities; accommodations; ADHD